Edward Bates papers - Bates, Edward, 1793-1869.
Correspondence, a diary, newspaper clippings, printed material, and other papers reflecting Bates's career in Missouri state politics and the U.S. House of Representatives and as U.S. attorney general. Includes memoranda read to President Lincoln's cabinet, Bates's opinion on the admission of West Virginia into the Union, and his statement entitled The Present Condition of the Country. Correspondents include C.R. Fritsch, Abraham Lincoln, and William T. Sherman.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Lawyer, politician, and U.S. attorney general.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Fritsch, C. R. -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Statehood (American politics); Missouri -- Politics and government; United States -- Politics and government -- 1815-1861.; United States -- Politics and government -- 1861-1865.; West Virginia -- Politics and government -- 1861-1865.; Cabinet officers; Lawyers; Politicians